Analysis of Service Quality with Servqual Method and Importance Performance Analysis in PT. XYZ - Syahputra, Ivan; Ismiyah, Elly; Rizqi, Akhmad (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
This research was conducted at the employee cooperative of PT. XYZ to identify the quality of service provided by the company cooperative to employees of PT. XYZ and provide suggestions for improving service quality which is the main priority for improvements. The method used in this research is the service quality method and Importance performance analysis with a quantitative observation model, this research begins in July 2023 - August 2023. The respondents in this research are all employees of PT. The sampling method was taken based on Slovin’s formulation and then the results were obtained from 95 people. The results of research that had been carried out throughout the GAP on five Servqual dimensions had negative values including tangible (-0.11), reliability (-0.35), responsiveness (-0.10), assurance (-0.11), and empathy (-0.39), so the entire gap has a negative value, namely employee satisfaction with the PT cooperative. XYZ has not been fulfilled. Corrective actions that must be implemented by the management of the PT employee cooperative. XYZ, based on the results of the Importance performance analysis on the Cartesian diagram, can be seen in quadrant A which is the quadrant with the main priority that needs improvement. There are 2 attributes in quadrant A including employees not looking at customer status in providing services (E2) and recording orders and transactions accurately (R2).